Soybean Resistance to White Mold: Evaluation of Soybean Germplasm Under Different Conditions and Validation of QTL - Kandel, Ramkrishna; Chen, Charles Y.; Grau, Craig R.; Dorrance, Ann E.; Liu, Jean Q.; Wang, Yang; Wang, Dechun (Frontiers in Plant Science, 2018)
Soybean (Glycine max L. Merr.) white mold (SWM), caused by Sclerotinia sclerotiorum (Lib) de Barry), is a devastating fungal disease in the Upper Midwest of the United States and southern Canada. Various methods exist to evaluate for SWM resistance and many quantitative trait loci (QTL) with minor effect governing SWM resistance have been identified in prior studies. This study aimed to predict field resistance to SWM using low-cost and efficient greenhouse inoculation methods and to confirm the QTL reported in previous studies. Three related but independent studies were conducted in the field, greenhouse, and laboratory to evaluate for SWM resistance. The first study evaluated 66 soybean plant introductions (PIs) with known field resistance to SWM using the greenhouse drop-mycelium inoculation method. These 66 PIs were significantly (P<0.043) different for resistance to SWM. However, year was highly significant (P<0.00001), while PI x year interaction was not significant (P<0.623). The second study compared plant mortality (PM) of 35 soybean breeding lines or varieties in greenhouse inoculation methods with disease severity index (DSI) in field evaluations. Moderate correlation (r) between PM under drop-mycelium method and DSI in field trials (r=0.65, p<0.0001) was obtained. The PM under spray-mycelium was also correlated significantly with DSI from field trials (r=0.51, p<0.0018). Likewise, significant correlation (r=0.62, p<0.0001) was obtained between PM across greenhouse inoculation methods and DSI across field trials. These findings suggest that greenhouse inoculation methods could predict the field resistance to SWM. The third study attempted to validate 33 QTL reported in prior studies using seven populations that comprised a total of 392 F4:6 lines derived from crosses involving a partially resistant cultivar ‘Skylla’, five partially resistant PIs, and a known susceptible cultivar ‘E00290’. The estimates of broad-sense heritability (h2) ranged from 0.39 to 0.66 in the populations. Of the seven populations, four had h2 estimates that were significantly different from zero (p<0.05). Single marker analysis across populations and inoculation methods identified eleven significant SSRs (p<0.05) corresponding to ten QTL identified by prior studies. Thus, these five new PIs could be used as new sources of resistant alleles to develop SWM resistant commercial cultivars.